La tablette hittite de Yozgat: exemple de copie récente - Masson, Emilia (1985)
photo de AO 4703. Editio princeps: A. H. Sayce - Th. C. Pinches, The Tablet from Yuzgat, in the Liverpool Institute of Archaeology, London 1907, Asiatic Society Monographs, vol. XI.